PERBEDAAN TINGKAT AKTIVITAS FISIK ANTARA REMAJA DESA DAN KOTA DI KABUPATEN BANYUMAS - Dicaraka, Benza Asa; Candrawati, Susiana; Wicaksono, Madya Ardi (Jurusan Kedokteran FK Unsoed, 2014)
Background: Physical activity is movement of the body produced by skeletal muscle contraction that increase energy expenditure. Low levels of physical activity or sedentary behavior is one of the behavioral tendency of the current world population. The research on levels of physical activity in adolescents in rural and urban areas have never done before. Although many differences between rural and urban are indirectly affect the level of physical activity.Objective: The aim of this study is to knowing the different levels of physical activity between rural and urban adolescents at Banyumas Regency.Methods: This study was conducted by using observational analytic cross sectional design with 72 adolescents as respondents. The respondents were high school students derived from 4 high schools of urban and rural area, 2 schools each. Each respondents from school of rural and urban were 36 respondents. Physical activity level was assessed with GPAQ questionnaire.Results: Analysis for the differences of physical activity level was using paired T-test analysis. Univariate analysis showed a mean rate of rural adolescentâs physical activity 2272.78Â±3165.26 MET/week and a mean rate of urban adolescentsâs physical activity 2321.89Â±2387.91. Bivariate analysis showed no significant differences of physical activity level between rural and urban adolescents (p=0,249).Conclusion: There was no different level of physical activity between rural and urban adolescents at Banyumas Regency